Smart capital mobilization in shared-use educational facilities: evidence from mega public universities - Van-Dam Vu; Minh-Anh Nguyen Thi; Van-Quynh Ha (Institute of Advanced Engineering and Science, 2026)
Although smart capital and shared facilities can improve efficiency in large public universities, many institutions still rely on fragmented paper-based management. This study evaluates how smart capital, integrating facilities, digital systems, and human readiness, drives behavioral change in shared facility management (FM). A survey of 246 staff members across multiple constituent units of a large Vietnamese public university system was conducted. The study integrates constructs from the technology acceptance model (TAM), technology readiness index (TRI), and information system (IS) success model. Partial least squares structural equation modeling (PLS-SEM) was employed to examine structural relationships and role-based differences. The results indicate that perceived ease of use (PEU) and system quality (SQ) significantly influence system use, while TRI affects adoption indirectly through PEU and perceived usefulness (PU). Differences between facility and academic staff highlight the importance of role-sensitive strategies for shared FM. This study provides an integrated framework for mobilizing smart capital in shared-use governance of mega public universities.